Perception of success among adults practicing various fighting arts - Ambroży, Tadeusz; Serafin, Natalia; Pawelec, Przemysław; Piepiora, Paweł Adam; Borysiuk, Zbigniew; Kindzer, Bogdan; Kasicki, Krzysztof; Rydzik, Łukasz; Cynarski, Wojciech J. (Frontiers in Psychology, 2024)
Problem statement Goal orientations, which influence learning and motivation, are categorized into task orientation (focused on skill development and personal mastery) and ego orientation (focused on outperforming others and gaining recognition). This study aims to explore how different demographics perceive success in martial arts. Approach and purpose The research questions focused on identifying correlations between perceptions of success and demographic factors: (1) sex, (2) age, (3) type of martial art practiced, and (4) nationality. These factors were examined to understand their impact on success perceptions among martial arts practitioners. Materials and methods The study utilized the Perception of Success Questionnaire (POSQ) to gather data from 268 participants—142 from Poland and 126 from Ukraine—selected through voluntary participation. Statistical analyses included standard deviation, coefficient of variability, Spearman’s rank correlation, and ANOVA for multifactor analysis. Results The study revealed a weak correlation between the type of martial art practiced and perception of success (rs = 0.38), indicating that the style of martial art has limited influence on success perception. There was a weak correlation between nationality and perception of success (rs = 0.20), suggesting cultural factors do not play a role. A strong correlation was found between age and perception of success (rs = 0.80), highlighting how perceptions evolve with age. A significant correlation was also found between sex and perception of success (rs = 0.90), which may reflect broader cultural patterns influenced by globalization. Conclusion While the study identifies important demographic correlations affecting perceptions of success in martial arts, the findings are constrained by the sample size and demographic distribution, which limits the generalizability of the results. Further research with a larger and more diverse sample is recommended to deepen understanding.